INTERNET AND VIRTUAL REALITY - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The question of the virtual reality is world view in its meaning, as it characterizes the relationship to reality and the man himself. So the purpose of this article is a philosophical analysis of the phenomenon and researching the antinomies that arise.